Rodent Communities in Thar Sand Dune Ecosystem - Prakash, Ishwar (Annals of Arid Zone, 2016)
The desert-adapted rodent species (Gerbil/us, Meriones) are found in a relative abundance in sand dune ecosystem of the Thar desert. Tatera indica is more common in the sandy plains recehing 100-400 mm annual rainfall, whereas Mil/ardia meltada and Golullda ellioti inhabit semi-arid zones. It is conjectured that the bandicoot, Balldicota bengalensis has invaded the south-eastern and northern parts of the desert in recent years, mainly due to escalation of irrigated agriculture. It is revealed that with the increasing aridity the body size of gerbils decreases and tail and ear length increases. G. gleadowi has been found to be the most desert-adapted rodent of the Indian Thar and is considered as the biological indicator of enhancing desertification processes. The most preponderant and omnipresent rodent. Meriones hurrianae in the sandy biome of Thar is a serious agent of soil erosion as it excavates about 61,500 kg stabilized soil sq. km-1 day-1 from its extensive burrow system. The loosely piled sand is quickly air borne due to strong desert winds.